1999
DOI: 10.1021/bi982892+
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hepatitis C Virus NS3 Protease and Helicase Activities through the Interaction with NS4A

Abstract: The hepatitis C virus nonstructural 3 protein (NS3) possesses a serine protease activity in the N-terminal one-third, whereas RNA-stimulated NTPase and helicase activities reside in the C-terminal portion. The serine protease activity is required for proteolytic processing at the NS3-NS4A, NS4A-NS4B, NS4B-NS5A, and NS5A-NS5B polyprotein cleavage sites. NS3 forms a complex with NS4A, a 54-residue polypeptide that was shown to act as an essential cofactor of the NS3 protease. We have expressed in Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 58 publications
3
62
4
Order By: Relevance
“…Although the HCV helicase has been analyzed both as an isolated fragment and as part of the full-length NS3 protein, the few studies that directly compared the HCV helicase with and without its attached protease have not noted clear differences (11,23,24). There are nevertheless several noteworthy differences between studies that utilize full-length NS3 and those that use recombinant HCV helicase lacking the protease domain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the HCV helicase has been analyzed both as an isolated fragment and as part of the full-length NS3 protein, the few studies that directly compared the HCV helicase with and without its attached protease have not noted clear differences (11,23,24). There are nevertheless several noteworthy differences between studies that utilize full-length NS3 and those that use recombinant HCV helicase lacking the protease domain.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies have not noted differences in helicase (11,23,41), RNA binding (42), or RNA replication assays (24) when NS3 was truncated to delete the protease. In early studies Heilek and Peterson (11), concluded that the protease domain had little or no effect on helicase activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The RNA-unwinding activity seems to be modulated by other viral proteins, e.g. NS5B (Jennings et al, 2008;Zhang et al, 2005) and NS4A (Gallinari et al, 1999).The helicase domain of NS3 can be methylated posttranslationally at Arg1493 (polyprotein) by protein arginine methyltransferase 1 (PMRT1) (Rho et al, 2001). …”
mentioning
confidence: 99%
“…The RNA-unwinding activity seems to be modulated by other viral proteins, e.g. NS5B (Jennings et al, 2008;Zhang et al, 2005) and NS4A (Gallinari et al, 1999).…”
mentioning
confidence: 99%